(untitled) (EAAE Annual Conference Proceedings, 2023)
What does it mean to ‘rescue’ a modernist project like the Bauhaus to envision a future? The pedagogical emphasis of the Bauhaus, which sat at the core of its approach to society and the role aesthetic and design practices could play in this, was one premised on learning through making, interdisciplinary practices and design as an enabler, not just mirror, of socio-cultural aspirations and ambitions. What is striking now, over a century later, is how this alternative model of education continues to be espoused as the future. Given the developments in gender and postcolonial studies and the politicisation of education models, this paper critically considers what the Bauhaus has come to symbolise over the past century and what elements of its approach might be critically expanding for the field of design education today.